Community-based study on renew or dropout status of social health insurance program in Bharatpur Metropolitan City, Chitwan - Subedi, Chandan; Paudel, Eak Narayan; Koirala, Subash; Ghimire, Harishchandra; Paudel, Amrita (Nepalese Journal of Insurance and Social Security, 2021)
Health insurance is emerging as the most preferred form of the health financing mechanism. Higher dropout puts a threat to governments target (Social health security program) of 100% enrolment by 2030.This study aimed at accessing the factors associated with current SHI status (renew or dropout) in Bharatpur metropolitan city. The community based descriptive cross-sectional study using face to face interview was carried out in Bharatpur Metropolitan city, Chitwan. Total 342 household heads that have enrolled in Social Health Insurance for past year are considered as a sample to describe the Renewal status among SHI Enroll household. We used Pearson’s chi-square test to investigate the effect of some explanatory variables on renewal and dropout status of SHI. Among 342 household enroll SHI scheme, there were 203(59.4%) Renewed for next year and 139(40.6%) household dropout SHI Scheme. Results shows that current status of SHI (renew or dropout) differ significantly with Sex of household head (P< 0.01), education status (P<0.01), family type (P < 0.01), highest level of education in family (P < 0.01)), presence of children (P < 0.001), presence of pregnant women in family (P = 0.009), presence of ageing population in family (P < 0.001), Disability in family (P = 0.016), Chronic disease in family (P < 0.01). The study concluded that the influence factors for Renew or Dropout status of SHI were: type of family, household education status, presence of children, pregnant women in family, the ageing population in family, presence of disability and chronic disease in the family.